Characteristic of Background Seismic Noise of Local Tarutung Earthquake Based on Power Spectral Density and Probabilistic Density Function Method - Sinambela, Marzuki; Hartoyo, Puji (JUKI : Jurnal Komputer dan Informatika, 2025)
An evaluation of four broadband BMKG stations' ambient seismic noise is provided. Knowing the seismic ambient noise tiers confirmed by a community of seismic stations is essential for earthquake monitoring and detection purposes in the Sumatra area. Waveform records from May 2020 are used to calculate the power spectral density and likelihood density characteristic (PSDPDF) for a single day when an excessive noise stage is detected. This study aims to assess the vertical channel of waveform data using waveform information in miniSEED and SAC architecture. Because of their low probability of occurrence, the method used permits the use of data contaminated with earthquakes (a 4.8 magnitude earthquake occurred on May 11, 2020, at Tarutung, North Sumatera, Indonesia) and other demanding signals. The results obtained are extremely important for assessing the overall performance of the current seismic broadband stations, evaluating the web page resolution of new stations, and modifying the detection settings for the computerized processing machine in the Indonesia Seismic Network. Compared to TTSM, TKSM, and RSSM stations, the noise at LSTM stations is weaker, but the likelihood of an increase increases at high frequencies. Cultural noise in human endeavors produces certain noise and fluctuation over extended periods of time, which is typically certified for the process of earthquake signals